MOLECULAR STRUCTURE OF GELATIN EXTRACTED FROM PARROT (Scarus sp) FISH SCALES - Jeszy Novianti Andakke; Inneke F M Rumengan; Hizkia H Y Nainggolan; Lasma R M E Parapat; Engel Pandey; Pipih Suptijah; Aldian Hein Luntungan (JURNAL PESISIR DAN LAUT TROPIS, 2020)
One of the protein molecules of fish scales is water soluble gelatin. Gelatin of fish scales could be best substitute of commercial available gelatin which derived from porcine and bovine. The purpose of this study was to determine the molecular structure of gelatin extracted from marine fish scale using Fourier transform infrared (FTIR) analysis, and to obtain the moisture content, pH and yield of gelatin. Samples were prepared from the wet and dried scales. As for the standard gelatin, the gelatin of the two samples are characterized with several types of amide groups. The two gelatin samples were slight different in absorption of wave length for amide A, B, I, II and III groups indicating the instability of the functional groups which may influence viscosity and gel strength. For the wet scales derived gelatin, the wave number absorption was found to be 3412 cm-1 (amide A), 2421 cm-1 (amide B), 1653 cm-1 (amide I), 1400 cm-1 (amide II), and 1001 cm-1 (amide III), while for the dried scales derived gelatin was 3435 cm-1 (amide A), 2920 cm-1 (amide B), 1635 cm-1 (amide I), 1404 cm-1 (amide II), and 1036 cm-1 (amide III). The wave number absorption of amide III of gelatin is smaller than the one of collagen, because gelatin is in form of single helix, not triple helix. The wet scales derived and dried scales derived gelatin show the moisture content of 15.0% and 13.7%, and yield of 2.33% and 2.43%, .respectively. For both samples, the pH value was 7. Key words : gelatin, fish scales, molecule structure, moisture, yield, pH Abstrak Salah satu dari molekul protein sisik ikan adalah gelatin larut air. Gelatin sisik ikan dapat menjadi pengganti terbaik dari gelatin komersial yang tersedia yang berasal dari babi dan sapi. Tujuan dari penelitian ini adalah untuk menentukan struktur molekul gelatin yang diekstrak dari sisik ikan laut menggunakan Analisis FTIR (Fourier Transform Infrared), dan untuk mendapatkan kadar air, pH dan rendemen gelatin. Sampel disiapkan dari sisik basah dan sisik kering. Adapun standar gelatin, gelatin dari kedua sampel ditandai dengan beberapa jenis gugus amida. Kedua sampel gelatin sedikit berbeda dalam penyerapan panjang gelombang untuk amida A, B, I, II dan III yang menunjukkan ketidakstabilan kelompok fungsional yang dapat mempengaruhi viskositas dan kekuatan gel. Untuk gelatin sisik basah, panjang gelombang serapan ditemukan pada 3412 cm-1 (amida A), 2421 cm-1 (amida B), 1653 cm-1 (amida I), 1400 cm-1 (amida II), and 1001 cm-1 (amida III), sedangkan untuk gelatin sisik kering adalah 3435 cm-1 (amida A), 2920 cm-1 (amida B), 1635 cm-1 (amida I), 1404 cm-1 (amida II), and 1036 cm-1 (amida III). Panjang gelombang serapan amida III pada gelatin lebih kecil dibanding kolagen, sehingga gelatin berbentuk single helix, bukan triple helix. Gelatin sisik basah dan sisik kering mengadung kadar air 15,0% dan 13,7%, rendemen 2,33% and 2,43%, secara berturut-turut. Untuk kedua sampel memiliki nilai pH 7. Key words : gelatin, sisik ikan, struktur molekul, kadar air, rendemen, pH